Dengue virus NS1 secretion is regulated via importin-subunit β1 controlling expression of the chaperone GRp78 and targeted by the clinical drug ivermectin - Solène Denolly; Hongbo Guo; Miriam Martens; Anna Płaszczyca; Pietro Scaturro; Vibhu Prasad; Kessiri Kongmanas; Nuntaya Punyadee; Adisak Songjaeng; Dumrong Mairiang; Andreas Pichlmair; Panisadee Avirutnan; et al. (mBio, 2023)
ABSTRACT Dengue virus (DENV) is a major human pathogen. An important pathogenicity factor is non-structural protein 1 (NS1) required for viral replication and secreted from infected cells. A clinical study indicated that the anti-parasitic drug ivermectin lowers NS1 blood levels without affecting viremia. Ivermectin targets nuclear transport by binding to importin-α, but how NS1 secretion in patients is suppressed by this drug is unknown. We show that ivermectin impairs folding and secretion of endoplasmic reticulum-luminal glycoproteins, including NS1. Proteomic analysis identified chaperones interacting with NS1, including GRp78 (78-kDa glucose-regulated protein, also known as HSPA5 or BIP). This chaperone increased in abundance on DENV infection via activation of the unfolded protein response (UPR). Ivermectin blocked the nuclear transport of transcription factors required for UPR, thus impairing GRp78 upregulation and NS1 secretion. Reduction of GRp78 and NS1 secretion was also observed in patients treated with ivermectin. These results link nuclear transport and its inhibition by ivermectin to folding and secretion of luminal glycoproteins, including DENV NS1. IMPORTANCE Dengue virus (DENV) is a major human pathogen that can cause hemorrhagic fever and shock syndrome. One important factor of DENV pathogenicity is non-structural protein 1 (NS1), a glycoprotein that is secreted from infected cells. Here we study the mode of action of the widely used drug ivermectin, used to treat parasitic infections and recently shown to lower NS1 blood levels in DENV-infected patients. We found that ivermectin blocks the nuclear transport of transcription factors required for the expression of chaperones that support the folding and secretion of glycoproteins, including NS1. Impairing nuclear transport of these transcription factors by ivermectin or depleting them from infected cells dampens NS1 folding and thus its secretion. These results reveal a novel mode of action of ivermectin that might apply to other flaviviruses as well.